Study of Properties of 146 , 148Nd Isotopes by Using IBM-1 Model (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The spectra, B(E2), B(E2) branching ratios and Potential energy surface are studied in the Interacting Boson Model (IBM-1). It is found that146,148Nd are in  the transition  region U(5)-O(6). The values of B(E2) are increased  and quadrupole moment are decreased when the neutron number increased, the branching ratios showed the isotopes in transition region U(5)-O(6). The potential energy surface (P.E.S) shows that 146,148Nd deformed and conductance of U(5)-O(6) and have vibrational mfeature.